The Impact of Monetary Policy on Loan and Deposit Rates in the Context of Limited Capital Mobility in Russia - Elizaveta P. Dobronravova (Финансовый журнал, 2025)
According to the macroeconomic theory, capital controls should improve the transmission of interest rates from the monetary policy rate to market-based short- and long-term rates, as the latter are less affected by global financial conditions. We test this hypothesis using the case of the Russian economy, which faces massive domestic and external restrictions on capital flows in 2022–2024. During this period, the pass-through of interest rates could be reduced: for long-term deposits — by the high level of uncertainty in the Russian economy, for credit rates — by broad preferential lending programs: mortgages, SME lending, agricultural lending, etc. The study was conducted using the error correction model, which is commonly used in modeling the pass-through of interest rates in the credit and deposit markets. Such a model allows us to estimate the short- and long-run effects of a change in the monetary policy rate, as well as the speed of adjustment to a new long-run equilibrium. Proxy variables for capital restrictions and preferential lending were included in the model as a change in the slope to the monetary policy rate. The results of the analysis show that both short- and long-run pass-throughs in the retail deposit market have intensified since March 2022. Moreover, when we add a control variable reflecting the extent of preferential lending, we are able to confirm our hypothesis for long-term interest rates on individual credits and short-term interest rates on credits to non-financial organizations. The expansion of preferential lending in most model specifications had a negative impact on the effectiveness of passthrough lending.